Immature Gastric Teratoma in a Newborn: A Case Report - Yoon, Seock Hwa; Park, Ga Young; Suh, Won Seok; Kim, Sung Shin; Hong, Hyun Sook (Neonatal medicine (Seoul, Korea), 2017)
A teratoma is the most common germ cell tumor in children; however, a gastric teratoma is very rare. An immature gastric teratoma has malignant potential; therefore, it should be removed surgically and followed up routinely to assess for recurrence by performing imaging studies and estimating serum alpha-fetoprotein (AFP) level. We describe the case of a 2-day-old male neonate with abdominal distension and a palpable mass. He underwent surgical resection of a tumor that was diagnosed as an immature gastric teratoma. KCI Citation Count: 0